Evaluation of Salivary Proteomic and Genomic Biomarkers as Non-Invasive Diagnostic Tools for Early Detection of Alzheimer's and Parkinson's Diseases: A Schematic Assessment and Meta-Analysis - Ayesha Mudasser; Mubina Laghari; Aman Ullah Siddiqui; Pakeeza Shafique Ul Rehman (Pakistan Journal of Medicine and Dentistry)
Background: Salivary biomarkers are non-invasive molecules that indicate neurodegenerative illnesses, especially Alzheimer disease (AD) and Parkinson disease (PD).this study was conducted to determine the diagnostic precision of salivary proteomic and genomic biomarkers in terms of early AD and PD detection.